Analysis of the Need for Development of Blended Learning Model in Early Childhood Education Programs in the Rejang Lebong Region - Kusen Kusen (STAI Hubbulwathan Duri, 2022)
This study aims to conduct a conditions analysis on developing a composite knowledge model in early childhood education programs in the Rejang Lebong area to grow character values and pupil literacy provocation. This disquisition is part of the RD (Research and Development) disquisition with the ADDIE model (analysis, design, development, performance, and evaluation). However, this research is only limited to the analysis stage, which is to analyze the need for the development of blended learning models in early childhood education programs education to grow character values and student learning motivation. The population in this study were all early childhood education programs teachers in the Rejang Lebong area. The samples taken were 75 people with the probability sampling technique. The study was conducted in October 2021. The instrument used in this study was a needs questionnaire made using a modified Likert scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. The results of this study are the blended learning model is a learning model needed by early childhood education programs teachers in the Rejang Lebong Regency area, especially during the covid-19 pandemic. This is evidenced by the percentage obtained from the teacher needs questionnaire analysis process, which reached 89.78%, which was categorized as strongly agree. For this reason, further research is needed to develop a blended learning model in early childhood education programs education in the Rejang Lebong area to grow character values and student learning motivation.